2007
DOI: 10.1161/circulationaha.106.665893
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Visfatin in Macrophages of Human Unstable Carotid and Coronary Atherosclerosis

Abstract: Background-Although the participation of inflammation in atherogenesis is widely recognized, the identification of the different components has not been clarified. In particular, the role of inflammation in plaque destabilization is not fully understood. Methods and Results-Our main findings were as follows: (1) In a microarray experiment, we identified visfatin, one of the most recently identified adipokines, as a gene that was markedly enhanced in carotid plaques from symptomatic compared with plaques from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
423
2
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 437 publications
(473 citation statements)
references
References 25 publications
32
423
2
16
Order By: Relevance
“…The key findings of Arq Bras Endocrinol Metab. 2014;58/1 human unstable carotid and coronary atherosclerotic lesions, where the influence of insulin sensitizers seems to be limited (8,21). The mechanisms cited above indicate that insulin sensitizers may have little effect on visfatin.…”
Section: Discussionmentioning
confidence: 99%
“…The key findings of Arq Bras Endocrinol Metab. 2014;58/1 human unstable carotid and coronary atherosclerotic lesions, where the influence of insulin sensitizers seems to be limited (8,21). The mechanisms cited above indicate that insulin sensitizers may have little effect on visfatin.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of pro-inflammatory role of visfatin, its potential effect in inflammation has gradually attracted much attention, especially in atherosclerosis, which is closely related with both lipid metabolism and inflammation (Yan et al 2010;Liu et al 2009). One of the most related studies has reported that visfatin should be considered as an inflammatory mediator, localized to foam cell macrophages within unstable atherosclerotic lesions, which potentially plays a role in plaque destabilization (Dahl et al 2007). Although it has been reported that visfatin is participated in the pathogenesis of atherosclerosis and may be involved in the early formation of foam cells, its exact effect is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have shown that PBEF interacts with the insulin receptor (8-10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).In vitro activation of signaling pathways by PBEF has been shown to regulate the expression of metalloproteinases, chemokines, and cytokines (6,7,(9)(10)(11)(12), but the in vivo contribution of this mediator of arthritis progression remains unclear. The recently developed small molecule inhibitor APO866 has been shown to act as a competitive inhibitor of PBEF/NAMPT activity by inhibiting binding of its natural substrate, nicotinamide (14,15).…”
mentioning
confidence: 99%
“…Several groups have shown that PBEF interacts with the insulin receptor (8-10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation